The Effectiveness of Providing Yoga Exercise Intervention with Islamic Spiritual Mindfulness Intervention on Anxiety Levels in Hypertension Patients at Ngoresan Health Center - Tika Alvio Nita; Maryatun; Irma Mustikasari; Hermawati (PT Inovasi Pratama Internasional, 2023)
Background: The elderly are more at risk or tend to experience various diseases that often arise, namely hypertension. High blood pressure can cause the risk of stroke, heart failure and death. This death causes the elderly to become worried about their condition, so that the elderly experience psychological changes, namely anxiety that requires long treatment and excessive worry. Anxiety can be overcome with non-pharmacological abortion interventions, namely Yoga and Islamic Spiritual Mindfulness. Purpose: This study aims to determine the effectiveness of Islamic Yoga and Spiritual Mindfulness therapy in reducing anxiety in elderly hypertension. Research Methods: This study used a Quasi-Experimental Design with a Control Group pretest-posttest Design approach, taking a sample of 60 respondents. The research instrument used the DASS questionnaire (Depression et al.). The results showed a significant value of Islamic Yoga and Spiritual Mindfulness Therapy on anxiety levels in elderly hypertensives with a p-value of 0.039 <0.05. The average Anxiety result in yoga practice was 26.33, and the average Anxiety result in Islamic spiritual Mindfulness practice was 22.93. The results showed that there was a significant value in Islamic Yoga and Spiritual Mindfulness Therapy on the level of anxiety in elderly hypertensives with a p-value of 0.039 <0.05, which means that there is an average difference between Islamic Yoga and Spiritual Mindfulness Therapy and anxiety levels. The average Anxiety result in yoga practice was 26.33, and the average Anxiety result in Islamic spiritual Mindfulness practice was 22.93. Conclusion: Yoga practice intervention is more effective than Islamic Spiritual Mindfulness therapy on the anxiety level of elderly hypertension. Conclusion: Yoga practice intervention is more effective than Islamic Spiritual Mindfulness therapy on the anxiety level of elderly hypertension